Sustainable thermoplastic elastomers: valorization of waste tires, recycled HDPE, and recycled EVA - Loor, Jose Suarez; Cordero, Miguel Carrasco; Lazo, Miriam; Adrian, Estephany; López, Angie Mendoza; Villalobos, Joan Vera; Cedeño, Andrés Rigail (Frontiers in Sustainability, 2025)
The present study focused on the comprehensive investigation of the properties of thermoplastic elastomeric composites (TPE) containing 70% by weight of ground tire rubber (GTR) and a range of 15 to 30% by weight of recycled polyethylene (rHDPE). To improve the properties of these composites, different percentages of recycled nylon fibers (rPA) and recycled ethylene vinyl acetate (rEVA) were incorporated as reinforcing and compatibilizing agent, respectively. It was found that composites containing 5% and 10% by weight of rEVA exhibited higher plastic deformation capacity (7.3%), lower stiffness, and higher impact strength (247.92 J/m). These results were attributed to lower interfacial tension between GTR and rHDPE, which allowed the rHDPE to be encapsulated in the GTR matrix, thus favoring these mechanical properties. A detailed scanning electron microscopy (SEM) analysis revealed that the considerable particle size of the GTR used had a negative impact by causing premature tearing of the TPEs and limited deformability. Furthermore, it was confirmed that incorporating rPA into the composites adversely affected the mechanical, physical, and processability properties. This was due to difficulties in the homogeneous dispersion of rPA fibers within the GTR matrix. Also, when analyzing the processability of the composites, a slight increase in processing torque was observed in the composites with rEVA, which was attributed to a slight crosslinking of these composites. In contrast, thermogravimetric tests did not evidence a significant variation in degradation temperatures; however, they showed that the processing temperature should be kept below 380°C. These results highlight the considerable potential of the composites developed, as they have been manufactured exclusively from 100% recycled raw materials, without any physical or chemical pre-treatment.